2010
DOI: 10.1007/s00586-010-1544-1
|View full text |Cite
|
Sign up to set email alerts
|

Cervical spondylotic amyotrophy

Abstract: Cervical spondylotic amyotrophy is characterized with weakness and wasting of upper limb muscles without sensory or lower limb involvement. Two different mechanisms have been proposed in the pathophysiology of cervical spondylotic amyotrophy. One is selective damage to the ventral root or the anterior horn, and the other is vascular insufficiency to the anterior horn cell. Cervical spondylotic amyotrophy is classified according to the most predominantly affected muscle groups as either proximaltype (scapular, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 44 publications
2
49
0
Order By: Relevance
“…This finding can be attributes to the AHs located in the terminal territory of the sulcal (central) arteries, which are considered the most vulnerable to the effects of circulatory insufficiency 1. Wada et al 20.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This finding can be attributes to the AHs located in the terminal territory of the sulcal (central) arteries, which are considered the most vulnerable to the effects of circulatory insufficiency 1. Wada et al 20.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers attribute the syndrome to the selective intradural compression of the ventral motor roots by posterolateral osteophytes 1. Others attribute it to a circulatory insufficiency in the territories of the spinal central arteries, as well as to selective damage to the AHs 1. Fujiwara et al 7.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…also reported that the distal type showed a greater number of involved vertebrae causing cord compression and a poorer outcome than the proximal type. By literatures review, we can find two possible reasons to interpret the distinct surgical outcomes919. One possible reason is the longer distance from the cervical spinal cord or nerve root to the atrophic muscles in distal type than in proximal type.…”
Section: Discussionmentioning
confidence: 99%